The Murray-Darling Basin shows why the ‘social cost of water’ concept won’t work - Wheeler, Sarah Ann; Ringler, Claudia (The Conversation, 2023)
Access to safe, clean water is a basic human right. But water scarcity or barriers to access can cause conflict within and between countries.